Evaluation of Recruitment Approaches for the HPTN 052 Clinical Trial of HIV Serodiscordant Couples in Rural Western Kenya - K. Ondeng’e; D. Gust; M. Nyikuri; A. Ogendo; R. Ndivo; R.T. Chen; K. F. Laserson; L. A. Mills (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
Recruitment of couples is important for study success. The multi-centered HPTN 052 clinical trial was designed to evaluate whether immediate versus delayed use of ART by HIV-infected individuals would reduce transmission of HIV to their HIV-uninfected partners. The objective of this study was to retrospectively compare several approaches for community recruitment at our site in Kisumu, Kenya based on a) feedback from recruitment staff, b) associated cost, and c) number of eligible couples enrolled. A secondary objective was to assess the discordant couples’ acceptability of the community recruitment approaches relative to the a) main recruitment venues, b) educational materials, and c) local language best suited for explaining the trial. 241 couples were screened for eligibility using nine recruitment approaches. We compared the approaches used for the 60 couples found to be eligible to those used for the 56 ineligible couples for whom that information was available. Analyses for association were carried out. In-depth interviews were conducted with 20 staff and 29 discordant couples. Records were kept of the costs associated with each approach. Overall, staff interviews revealed that acceptability of the approaches was high. Challenges were present with all approaches ranging from one member of the couple not wanting to reveal their positive HIV status to their partner (Patient Support Center or PSC approach), to not finding people at home (home based counseling and testing or HBCT approach). The PSC and the HBCT recruitment approaches were the most effective in terms of recruiting eligible participants. There was an overall significant difference between the proportion of eligible and ineligible participants among the 9 approaches (χ2 (8) =33.5; p<0.0001). Analyses for association showed that the PSC approach resulted in attracting a greater proportion of couples who were eligible than ineligible (χ2 (1) =6.6; p=0.016). The cost for the PSC approach was less than one-third that of the HBCT approach. All discordant couples interviewed found the two main recruitment venues (PSC and their home) acceptable. Among couples who saw the educational materials, the majority found them useful (poster 72.7%; pamphlet 90.9%; flyer 88.9%). All couples found the language they were told about the study acceptable. The evaluation of recruitment approaches indicated that working with local partners, specifically the PSC staff and HBCT staff, was the most effective way to recruit eligible discordant couples. A focus on collaborations and partnerships between research and clinical organizations will help study recruitment efforts. Disclaimer: The findings and conclusions in this report are those of the authors and do not necessarily represent the views of their respective institutions. Funding for this substudy was provided by the Kenya Medical Research Institute (KEMRI) through a cooperative agreement with the U.S. Centers for Disease Control and Prevention.
Keywords: community recruitment